LE EVINOSPONGE: IPOTESI GENETICHE DI CEMENTI CALCITICI NELLA PIATTAFORMA LADINICA DELLE PREALPI LOMBARDE (ALPI MERIDIONALI) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The "evinosponge" are globose structures, both isolated and in anastomotic groups, whose size ranges from a few centimeters up to 3 meters. Each structure consists of several isopachous concentric crusts composed of low-Mg calcite crystals arranged in pseudofibres. Individual calcite crystals show irregular intercrystalline boundaries, deformed twins and cleavages and strong undulose extinction. Located within the medium-upper part of the ladinian Esino Limestone, the "evinosponge" are distinctive of those facies, such as open subtidal, prograding margin and slope, which are characterised by a high primary porosity and are facing the deep basins of the W engen Formation. Although the "evinosponge" are not pervasive in all the Esino Limestone platform margins, they represent up to the 70% of the whole rock in some areas. Formerly interpreted as fossil organisms (Stoppani, 1858), the "evinosponge" are here considered typical reef cements whose morphology developed through processes of dissolution and reprecipitation during early to burial diagenetic stages. The dissolution and reprecipitation processes took place in a mixed marine-meteoric water environment characterised by continuous changes in the chemical composition of the pore fluids and consequent fluctuations in carbonate saturation state. Furthemore, organisms such as the Tubiphytes and the Spongiostromata contributed to the development of the "evinosponge" acting as cement catalysts. Through the effects of perspiration and decaying organisms were also responsible for changes in the pore fluid chemistry towards undersaturation with respect to the more unstable phase of CaCO3. The cavity filling fibrous cements of the "evinosponge" underwent late diagenetic homogeneisation and crystal deformation which conferred random optical characters to the calcite pseudofibres.
Keywords: Carbonate platform cements; Diagenesis; Ladinian; Southern Alps; Italy.